ANALISIS PENGARUH RADIUS BENDING TERHADAP PERFORMANSI JARINGAN TRANSMISI SERAT OPTIK PADA JARINGAN FIBER TO THE HOME (FTTH) - Rahadian, Hanif Azmi; Partiansyah, Fakhriy Hario; Mustofa, Ali (Jurnal Mahasiswa TEUB, 2024)
The development of global telecommunication technology, particularly the increasing demand for fast and reliable internet connections, has driven the adoption of fiber optic networks in Indonesia. Fiber optics, made from fine glass or plastic, provide a solution for data transmission due to their reliability and ability to carry large amounts of data at high speeds. However, one of the challenges in fiber optic installation is bending, which can lead to signal attenuation or loss. This research will conduct experiments on the effects of bending in FTTH networks, specifically focusing on power loss and bending loss due to macrobending. The experiment will be carried out by varying the bending radius, number of loops, and cable length to measure the impact on network performance using OPM and OTDR. The results of this study indicate that as the number of loops increases and the bending radius decreases, power loss becomes greater. This research will provide power link budget calculations, which will be compared with power measurements at the ONT to determine which power link budget results meet ITU-T standards. Additionally, bending loss measurements will be conducted to identify the attenuation that occurs.Keywords: Fiber Optic Communication, Bending, Power Loss, Bending Loss, Power Link Budget